SELF-DETERMINATION OF YOUTH WITH MILD INTELLECTUAL DISABILITY: A STUDY ON TEACHERS’ VIEWS AND PRACTICES - Güntülü Tercanlı Metin; Kasım Karataş (International Journal of Eurasia Social Sciences, 2024)
Self-determination, which is generally defined in the field of disability as the right of individuals to have control over their lives and a combination of knowledge, skills and beliefs required to exercise this right, has an important role in the personal, social, employment and academic attainments of individuals with intellectual disabilities. This study aims to address this issue, which has just begun to take place in the literature of our country, from the perspective of special education teachers working in special education vocational schools and to reveal the knowledge, views and practices of them regarding the self-determination of young people with mild intellectual disabilities. The study was designed with qualitative research method based on phenomenological approach. Semi-structured interviews were conducted with 13 special education teachers in five different special education vocational schools in Istanbul. The data were analyzed using MAXQDA 2020 qualitative data analysis program, and coded and categorized under the themes of Knowledge on Self-determination, Views on Self-determination, and Views on School and Self-determination. As a result of the analysis, it was found that most of the special education teachers are not familiar with the concept of self-determination and the majority of the their students having mild intellectual disability do not have enough self-determination skills and opportunities. In addition, it is seen that there are individual, familial and socio-political barriers to the self-determination of young people with mild intellectual disabilities and the educational practices in special education vocational schools do not sufficiently support the self-determination of young people. In line with these findings, recommendations for service areas including education, research, interventions and policies for youth with intellectual disabilities are presented.